Genetic evidence for assortative mating on alcohol consumption in the UK Biobank - Laurence J. Howe (Nature Portfolio, 2019)
From observational studies, alcohol consumption behaviours are known to be correlated in spouses. Here, Howe et al. use partners’ genotypic information in a Mendelian randomization framework and show that a SNP in the ADH1B gene associates with partner’s alcohol consumption, suggesting that alcohol consumption affects mate choice.